Prenylated Benzene Metabolites from Melicope pteleifolia. Issue 1 (22nd January 2013) - Yang, Li‐Jun; Jiang, Kun; Tan, Jun‐Jie; Qu, Shi‐Jin; Luo, Hong‐Feng; Tan, Chang‐Heng; Zhu, Da‐Yuan
Abstract Chemical investigation on the stem and root of Melicope pteleifolia afforded three new prenylated benzene metabolites as racemic mixtures, named pteleifolins A–C (1–3, resp.). Their gross structures were elucidated on the basis of spectroscopic analysis, especially 2D‐NMR experiments. An enantiomer resolution of (±)‐1 using chiral HPLC was performed, and the absolute configuration of the enantiomers were determined to be (+)‐(S)‐1 and (−)‐(R)‐1 by means of circular‐dichroism analysis.